Responsible consumption: an inquiry into behaviours, values and attitudes of Singaporean consumers towards sustainability, especially towards food waste and sustainable fashion, from the Millennial generation - Vu, Hoai Thu (2023)
Coronavirus pandemic is a once in a century global crisis that devastated many lives and economies across the whole world. The Covid-19 pandemic has forced the global consumers’ behaviours to alter in many big and small ways, and at the same time, caused global consumers to be more concerned on the health related issues and the environmental impacts of their own purchasing decisions and shopping choices. The main aim of this study is to provide empirical evidence of how the current pandemic changes consumer choices related to sustainability, specifically to food waste and to sustainable fashion, compared to the time before the pandemic.